Analyses of the stress intensity of the cylindrical tank wall at the place of the geometrical defect - Rasiulis, Konstantin; Gurkšnys, Kęstutis (Journal of Civil Engineering and Management, 2010)
Major repair or regular inspection of the large capacity thin‐walled tankages is very expensive. Steel cylindrical tanks are an individual case of the thin‐walled tankages. The common calculation of the tanks by analytical and numerical methods is not difficult. Strengthening the places, where a perfect calculated form is disturbed, that is, at the spots of in‐cuts, hatches, defects etc. is a responsible part of the design of such constructions. The problems of prevention of defects during the operation period and repairs, as well as possibility to assure quickly the safety of defective places of the constructions are more important than the common calculations. The main objective of the presented investigations is to identify stress/strain state of the wall tank with local imperfections from the ideal cylindrical surface, taking into account the membrane theory of the shells by using the finite element’s method. First Published Online: 24 Jun 2011